(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Objective: The objective of the study is to evaluate the diagnostic yields of endoscopic retrograde cholangiopancreatography (ERCP) done on previously unexamined section of Bangladeshi population having suspected hepatobiliary and pancreatic diseases. Methods: Patients were selected retrospectively having suspected hepatobiliary and pancreatic diseases with characteristic findings of clinical, laboratory and imaging examinations. ERCP was performed using Pentax Duodenoscope (ED 3440T), Siemens (Siremobil Compact) fluoroscope and Microvasive accessories following standard guidelines. Results: Six hundred and thirty-five patients were suspected to have hepatobiliary and pancreatic diseases during the last 5-year period. All patients had undergone ERCP which revealed 25.2% having choledocholithiasis and 24.2% having biliary ascariasis. Interestingly, both of these diseases were found in more than 73% of female patients. Conclusion: This first report of ERCP on previously unexamined population of southeastern part of Bangladesh showed high incidences of choledocholithiasis and biliary ascariasis in predominantly female patients. High association of biliary ascariasis with choledocholithiasis in female patients might further be evaluated. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.18 Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 13.